Searching for bioactive compounds from Solanaceae: lethal and sublethal toxicity to Spodoptera frugiperda and untargeted metabolomics approaches - Lima, Andreísa Fabri; do Prado Ribeiro, Leandro; Gonçalves, Gabriel Luiz Padoan; Maimone, Naydja Moralles; Gissi, Danilo Soares [UNESP]; de Lira, Simone Possedente; Vendramim, José Djair (Springer Nature, 2021)
The fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is a major pest of maize crops and others row crops on the American continent, and this pest has spread to Africa and Asia. Such lepidopteran pest presents resistant populations to synthetic insecticides and to Bacillus thuringiensis (Bt) toxins and, consequently, new (bio) insecticides with distinct modes of action are required. In order to search for derivatives from Solanaceae as a potential source of bioactive compounds, a screening of 38 ethanolic extracts were prepared from 25 Solanaceae species. Using dietary exposure assessment, the ethanolic extracts from leaves of Acnistus arborescens (L.) Schltdl. and Datura stramonium L. were the most promising derivatives. A bioguided fractionation was performed with both plant species. The A. arborescens dichloromethane fraction was the most active, causing sublethal (growth inhibition) and lethal toxicity. Thus, this fraction was submitted to another fractionation procedure resulting in three subfractions (dichloromethane, ethyl acetate and methanol) that were tested against S. frugiperda caterpillars. All subfractions lead to significant sublethal effects, however, without significant mortality. The chemical diversity in the subfractions of A. arborescens was assessed through untargeted approaches, such as molecular networking and the in silico annotation tool NAP, by which two withanolides glycosides were annotated: (22R)-1-Oxo-3beta-(beta-D-glucopyranosyloxy)-14,20,22,27-tetrahydroxyergosta-5,24-diene-26-oic acid delta-lactone and withanoside XI. Therefore, derivatives of Solanaceae present promising compounds that may be useful in the framework of S. frugiperda integrated pest management. In addition, metabolomics is an innovative alternative and powerful approach to facilitate the putative identification of compounds in studies of natural products.
Keywords: Acnistus arborescens; Botanical insecticides; Chromatographic procedures; Datura stramonium; Fall armyworm; Withanolides